Facing Legal Uncertainty: Challenges of Corporate Law and Environmental Regulation for Sustainable Business Practices in Indonesia - Riyan Al Fajri (Journal of Social Research, 2025)
This study explores the challenges posed by legal uncertainty in corporate law and environmental regulations that affect sustainable business practices in Indonesia. As the country seeks to balance economic growth with environmental protection, the absence of clear guidelines for environmental, social, and governance (ESG) practices makes it difficult for businesses to adopt sustainable operations. Key issues contributing to this legal uncertainty include conflicting regulations, frequent changes to laws, and inconsistent enforcement, all of which can undermine business confidence and hinder innovation. The Omnibus Law, introduced in 2020 to simplify investment processes, has raised concerns about weakening environmental protections, complicating compliance for businesses. Using a normative research approach, this study reviews existing literature to identify and analyze the connections between various legal frameworks. The findings suggest that creating a Comprehensive Legal Framework for Sustainability, establishing a Regulatory Oversight Body, and improving stakeholder engagement are crucial steps to reduce legal uncertainty and encourage sustainable practices. By aligning environmental regulations with industrial policies, Indonesia can create a more stable legal environment that supports sustainable development.